Inflation targeting and regional inflation persistence: Evidence from Korea - Peter Tillmann (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
The adoption of a credible monetary policy regime such as inflation targeting is known to reduce the persistence of inflation fluctuations. This conclusion, however, is derived from aggregate inflation or sectoral inflation rates, not from regional inflation data. This paper studies the regional dimension of inflation targeting, i.e. the consequences of inflation targeting for regional inflation persistence. Based on data for Korean cities and provinces it is shown that the adoption of inflation targeting leads (i) to a fall in inflation persistence at the regional level and (ii) to a reduction in the cross-regional heterogeneity in inflation persistence. A common factor model lends further support to the role of the common component, and hence monetary policy, for regional inflation persistence.
Keywords: E31; E52; R11; 330; inflation targeting; inflation persistence; monetary policy regime; regional inflation; factor model; Inflation Targeting; Wirkungsanalyse; Inflation; Region; Hysteresis; Südkorea